Chronotopes and stereotypes in advertising fiction. An analysis of the identification of the receptor with the advertising story - García López, Javier; Hellín Ortuño, Pedro A. (Historia y Comunicación Social, 2014)
In the advertising story there are two main components to the receiver is identified. They are the chronotope and stereotypical characters. The aim of this paper is to analyze how these narrative categories impose limits on the advertising text audience’s decoding. For this purpose we develop a content analysis of 612 television adverts (2009-2013). The research results show that the relations and scenes represented offer the receiver hopes of a better life; they offer a fiction world that allows individuals to identify with the dream of experiences that improve their current conditions. However, these new experiences are only possible through the use of advertised objects.
Keywords: TV Advertising; chronotope; characters; stereotypes